The Protein Expression of PDL1 Is Highly Correlated with Those of eIF2α and ATF4 in Lung Cancer - Hua, Chung-Ching; Kuo, Wei-Ke; Chen, Tzu-Ping; Chang, Liang-Che (Disease markers, 2018)
Introduction. The expression of programmed death 1 (PD1) and programmed death ligand 1 (PDL1) can be induced by the interferon (IFN)/signal transducer and activator of transcription (STAT) pathway. The PD1/PDL1 reverse signaling can activate the eukaryotic translation initiation factor 2 (eIF2α)/activating transcription factor 4 (ATF4) pathway which in turn regulates the expression of IFN regulatory factor (IRF) 7 and IFNα. The eIF2α/ATF4 pathway is responsible for the integrated stress response (ISR) of unfolded protein response (UPR) which can affect immune cell function in tumor microenvironment. Materials and Methods. The protein levels of PDL1, IRF1, IRF7, STAT1, STAT2, IFNAR1, eIF2α, and ATF4 in the normal and tumor tissues of 27 subjects with lung cancer were determined by Western blot. Results. The protein level of PDL1 was significantly correlated with those of IRF1, eIF2α, and ATF4 in the tissues of all subjects and the subgroup of squamous cell carcinoma but not in the normal tissue of adenocarcinoma. The protein levels of IRF1, eIF2α, and ATF4 were consistently correlated in the tumor tissues but to various extents in the normal ones. The protein level of PDL1 was not correlated with those of STAT1 and STAT2 in all the tissues. Conclusion. The PDL1 expression in lung cancer may be independent of STAT1 and STAT2. The PD1/PDL1 axis and UPR/ISR may be closely associated in the tumor tissues of lung cancer.